Corporate Governance Mechanisms and Board Characteristics as Determinants of Financial Failure: A Cox Proportional Hazards Model (European Journal of Pure and Applied Mathematics, 2025)
This study aims to predict corporate failure (CF) using the statistical forecasting method, employing R. It also seeks to investigate the impact of corporate governance mechanisms (CG) and the characteristics of board directors (BC) on CF. The study examined 480 annual reports from industrial and service firms listed on the Palestine and Jordan Stock Exchange markets, totaling 7,200 inputs. The research utilized a survival approach and the Cox hazard regression model. The study found a significant negative association between board size, board independence, board education, board age, firm size, and liquidity, considered together, and CF. Conversely, there is a significant positive association between profitability and CF. The log-likelihood test results indicated that the CG and BC models are significant. To the authors' knowledge, this study is the first in Palestine and Jordan to focus on the statistical prediction of financial failure, bridging a gap in the existing literature by understanding the association between governance indicators and board features on one hand, and financial failure on the other. Additionally, this study distinguishes itself as one of the pioneering studies within the accounting domain to adopt a survival approach, traditionally prevalent in medical research. It is also one of the few researches that use the R Language in the accounting and business field.